Desenvolvimento de método para determinação de resíduos de pesticidas em frutas exóticas por dispersão da matriz em fase sólida e cromatografia líquida de alta eficiência com detector espectrofotométrico de absorção no UV-VIS com arranjo de diodos - Fróes, Márcia Beatriz Reis (2010)
The fruits are an excellent source of nutrition, providing significant health benefits. The consumption of fruits with new flavors and high nutritional characteristics, called superfruits has been a worldwide trend, among them are assai and cupuassu. The presence of pesticide residues in food is a risk to the population's health. For this reagor, it is important to develop analytical methods for pesticide residues determination. The literature does not describe method for determination of pesticides in assai and cupuassu. In this context, this work aims to develop a new method based on MSPD and HPLC-UV/DAD determination of bromuconazole, fenbuconazole, parathion methyl, kresoxm-methyl and teflubenzuron in exotic fruits, assai and cupuassu. The extraction method based on matrix solid phase dispersion was developed and validated using different types and amounts of sorbents (neutral alumina, Florisil, silica and C18) and organic solvents (15-30 mL) ethyl acetate, dichloromethane, cyclohexane and acetonitrile. The best results for bromuconazole, fenbuconazole, parathionmethyl and kresoxim-methyl by HPLC-UV/DAD analysis were obtained using 1:3 (w / w) sample: the solid support (neutral alumina) ratio, without clean-up, and eluted with 20 mL of ethyl acetate: cyclohexane 1:1, v / v ratio. For assai, recovery values ranged from 57 to 119% with coefficients of variation values ranging from 1.4 to 20% for concentration levels 1, 2 and 6 μg mL-1. Detection and quantification limits ranged from 0.1 to 0.9 μg g-1 and 0.4 to 2.1 μg g-1, respectively. For cupuassu, recovery values were between 57-69%, the concentration level of 2 μg g-1.